2016
DOI: 10.1007/978-1-4939-3332-7_29
|View full text |Cite
|
Sign up to set email alerts
|

Hairy Root Cultures of Gymnema sylvestre R. Br. to Produce Gymnemic Acid

Abstract: Gymnema sylvestre R. Br. (Asclepiadaceae) is an endangered species extensively used in the management of diabetes, obesity, and treatment of various diseases. Uncontrolled exploitation to meet the increasing demand and low seed viability hastens the disappearance of the plant from its natural habitat. Hairy root culture provides a suitable alternative for the enhanced production of active principles. The current protocol provides the optimized culture conditions for the establishment of hairy root cultures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The use of hairy root cultures for the production of bioactive compounds in pharmaceuticals has been extensively reported in literature. For instance, studies have shown that S. bulleyana hairy roots can be used to produce polyphenolic compounds (Wojciechowska et al, 2020), Trachyspermum ammi hairy roots can produce thymol (Vamenani et al, 2020), Gymnema sylvestre hairy roots can produce gymnemic acid (Rajashekar et al, 2016), Artemisia hairy roots can produce phenol, avonoid, sterol, and essential oil (Mottaki et al, 2019). Furthermore, Salvia viridis hairy roots can be utilized to produce polyphenolic compounds (Grzegorczyk-Karolak et al, 2018), Brugmansia candidas hairy roots can produce tropane alkaloids (Cardillo et al, 2016), Rehmannia elata hairy roots can produce iridoid and phenylethanoid glycosides (Piątczak et al, 2019), and Corylus avellana hairy roots can produce saponins (Jalalipour .…”
Section: Discussionmentioning
confidence: 99%
“…The use of hairy root cultures for the production of bioactive compounds in pharmaceuticals has been extensively reported in literature. For instance, studies have shown that S. bulleyana hairy roots can be used to produce polyphenolic compounds (Wojciechowska et al, 2020), Trachyspermum ammi hairy roots can produce thymol (Vamenani et al, 2020), Gymnema sylvestre hairy roots can produce gymnemic acid (Rajashekar et al, 2016), Artemisia hairy roots can produce phenol, avonoid, sterol, and essential oil (Mottaki et al, 2019). Furthermore, Salvia viridis hairy roots can be utilized to produce polyphenolic compounds (Grzegorczyk-Karolak et al, 2018), Brugmansia candidas hairy roots can produce tropane alkaloids (Cardillo et al, 2016), Rehmannia elata hairy roots can produce iridoid and phenylethanoid glycosides (Piątczak et al, 2019), and Corylus avellana hairy roots can produce saponins (Jalalipour .…”
Section: Discussionmentioning
confidence: 99%